Catechol-O-Methyltransferase Genotypes and Parenting Influence on Long-Term Executive Functioning After Moderate to Severe Early Childhood Traumatic Brain Injury: An Exploratory Study. Issue 6 (November 2017) - Kurowski, Brad G.; Treble-Barna, Amery; Zang, Huaiyu; Zhang, Nanhua; Martin, Lisa J.; Yeates, Keith Owen; Taylor, H. Gerry; Wade, Shari L.
Abstract : Objectives: To examine catechol- O -methyltransferase (COMT) rs4680 genotypes as moderators of the effects of parenting style on postinjury changes in parent behavior ratings of executive dysfunction following moderate to severe early childhood traumatic brain injury. Setting: Research was conducted in an outpatient setting. Participants: Participants included children admitted to hospital with moderate to severe traumatic brain injury ( n = 55) or orthopedic injuries ( n = 70) between ages 3 and 7 years. Design: Prospective cohort followed over 7 years postinjury. Main Measures: Parenting Practices Questionnaire and the Behavior Rating Inventory of Executive Functioning obtained at baseline, 6, 12, and 18 months, and 3.5 and 6.8 years postinjury. DNA was collected from saliva samples, purified using the Oragene (DNA Genotek, Ottawa, Ontario, Canada) OG-500 self-collection tubes, and analyzed using TaqMan (Applied Biosystems, Thermo Fisher Scientific, Waltham, Massachusetts) assay protocols to identify the COMT rs4680 polymorphism. Results: Linear mixed models revealed a significant genotype × parenting style × time interaction ( F = 5.72, P = .02), which suggested that the adverse effects of authoritarian parenting on postinjury development of executive functioning were buffered by the presence of the COMT AA genotype (lower enzyme activity, higher dopamine levels). There were no significant associations of executive functioning with the interaction between genotype and authoritative or permissive parenting ratings. Conclusion: The lower activity COMT rs4680 genotype may buffer the negative effect of authoritarian parenting on long-term executive functioning following injury in early childhood. The findings provide preliminary evidence for associations of parenting style with executive dysfunction in children and for a complex interplay of genetic and environmental factors as contributors to decreases in these problems after traumatic injuries in children. Further investigation is warranted to understand the interplay among genetic and environmental factors related to recovery after traumatic brain injury in children.